Long-term air pollutants exposure and respiratory mortality: A large prospective cohort study - Zhi-Hao Li; Xiao-Meng Wang; Dan-Qing Liao; Qian Zhang; Zi-Ting Chen; Cheng-Shen Qiu; Xu-Lian Tang; Hong-Min Li; Li-Ying Du; Pei-Dong Zhang; Dong Shen; Xi-Ru Zhang; et al. (Ecotoxicology and Environmental Safety, 2024)
Ambient air pollution is a major global health concern. Yet, no study has thoroughly assessed its link to respiratory mortality. Our research evaluated the combined and individual effects of air pollutants on respiratory mortality risks based on the UK Biobank. A total of 366,478 participants were studied. A Cox proportional hazards model was used to estimate the respiratory mortality risk from combined long-term exposure to five pollutants, summarized as a weighted air pollution score. During a median of 13.6 years of follow-up, 6113 deaths due to respiratory diseases were recorded. The hazard ratios (HRs) and 95% confidence intervals (95% CIs) of respiratory diseases were 2.64 (2.05–3.39), 1.62 (1.23–2.12), 2.06 (1.73–2.45), 1.20 (1.16–1.25), and 1.07 (1.05–1.08) per 10 μg/m3 increase in PM2.5, PM2.5–10, PM10, NO2, and NOx, respectively. The air pollution score showed a dose-response association with an elevated respiratory mortality risk. The highest versus lowest quartile air pollution score was linked to a 44% increase in respiratory mortality risk (HR 1.44, 95% CI: 1.33–1.57), with consistent findings in subgroup and sensitivity analyses. Long-term individual and joint air-pollutant exposure showed a dose-response association with an increased respiratory mortality risk, highlighting the importance of a comprehensive air-pollutant assessment to protect public health.